1-Butyl-3-methylimidazolium acetate pretreatment of giant reed triggering yield improvement of biohydrogen production via photo-fermentation. (November 2022) - Zhang, Quanguo; Shui, Xuenan; Awasthi, Mukesh Kumar; Zhang, Tian; Yang, Jiabin; Zhang, Huan; Chen, Zhou; Zou, Caihong; Jiang, Danping
Highlights: [Bmim]acetate pretreatment was applied to giant reed biomass for H2 production. Pretreatment temperature was not positively correlated with HY. The optimal [Bmim]acetate pretreatment condition enhanced the HY by 61.7 %. Retention time had the strongest effect on delignification, sugar yield, and HY. Abstract: Ionic liquids (ILs) have been considered as promising alternatives to traditional reagent for lignocellulosic biomass pretreatment because of their tunable physicochemical and "green" properties. In the study, the influence of 1-Butyl-3-methylimidazolium acetate ([Bmim]acetate) pretreatment of giant reed on H2 yield improvement via photo-fermentation (PF) was evaluated. Under the optimal pretreatment conditions (6 g/L [Bmim]acetate at 70 °C for 4 h), the delignification of giant reed was up to 26.7 %. In addition, the sugar yield (9.5 g/L) and hydrogen yield (72.3 mL/g TS) from giant reed were enhanced by 1.7-fold and 61.7 % over those of untreated giant reed, respectively. Moreover, ternary analysis showed that retention time had the strongest effect on delignification, sugar yield and hydrogen yield of giant reed compared to pretreatment temperature and [Bmim]acetate loading. These experimental results indicated that [Bmim]acetate pretreatment of giant reed is an effective approach to enhance the hydrogen yield via PF.